Conditions of Criminal Procedural Work - الشمري, كاظم عبد الله; اسماعيل, شاكر نوري (Journal of Legal Sciences, 2019)
In the event of a crime, a right to society arises in the imposition of the penalty by the perpetrator of the crime, through the criminal case, as it is the only way to do so. The acts carried out by the parties to the criminal proceedings, whether they are the litigants or others, are referred to as procedural actions. Directly any procedural action given only the availability of conditionsthese conditions on the two communities: the first objective and the second formality, may relate to those conditions that the person who initiates the procedural or procedural work itself and can not work procedural to produce its impact if one of his conditions. The importance of these conditions of the importance of the rules of criminal procedure since the application of those conditions are achieved balancing the interest of the community in the signing of the penalty and the interest of individuals in their personal freedoms and this is what we discussed in this discussion in the discussion of some of the criminal procedural rules in the Code of Criminal Procedure Iraq and found that the Iraqi legislator has improved In laying down the conditions of criminal procedural work, but he did not take a general theory  of invalidity as a procedural sanction to sign the procedural action contrary to its terms.